2014
DOI: 10.1021/jm401622k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Preclinical Characterization of 1-Methyl-3-(4-methylpyridin-3-yl)-6-(pyridin-2-ylmethoxy)-1H-pyrazolo-[3,4-b]pyrazine (PF470): A Highly Potent, Selective, and Efficacious Metabotropic Glutamate Receptor 5 (mGluR5) Negative Allosteric Modulator

Abstract: A novel series of pyrazolopyrazines is herein disclosed as mGluR5 negative allosteric modulators (NAMs). Starting from a high-throughput screen (HTS) hit (1), a systematic structure-activity relationship (SAR) study was conducted with a specific focus on balancing pharmacological potency with physicochemical and pharmacokinetic (PK) properties. This effort led to the discovery of 1-methyl-3-(4-methylpyridin-3-yl)-6-(pyridin-2-ylmethoxy)-1H-pyrazolo[3,4-b]pyrazine (PF470, 14) as a highly potent, selective, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Several in vitro and in vivo studies have supported the putative involvement of mGluR-mediated signaling on progression, aggressiveness, and recurrence of malignant gliomas, which points to the notion that specific subtype-selective mGluR ligands may be considered as potential adjuvant chemotherapy for glioma treatment. Several academic groups [116118], Pfizer [119], Roche [120, 121], Novartis [122] and Merck [123] have employed receptor structure-based design of mGluR selective negative allosteric modulators (NAMs) in their studies and ligand-receptor binding models were refined using mutagenesis and structure-activity data. Even though pharmaceutical and toxicological properties of all mGluR ligands are not yet entirely determined for humans (such as effective and maximum tolerable doses), several clinical studies on Phase I, II and III are being performed using mGluR modulators for treatment of distinct brain disorders and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have supported the putative involvement of mGluR-mediated signaling on progression, aggressiveness, and recurrence of malignant gliomas, which points to the notion that specific subtype-selective mGluR ligands may be considered as potential adjuvant chemotherapy for glioma treatment. Several academic groups [116118], Pfizer [119], Roche [120, 121], Novartis [122] and Merck [123] have employed receptor structure-based design of mGluR selective negative allosteric modulators (NAMs) in their studies and ligand-receptor binding models were refined using mutagenesis and structure-activity data. Even though pharmaceutical and toxicological properties of all mGluR ligands are not yet entirely determined for humans (such as effective and maximum tolerable doses), several clinical studies on Phase I, II and III are being performed using mGluR modulators for treatment of distinct brain disorders and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pfizer has reported an instance of biliary epithelial hyperplasia in a NHP toxicology study with an alkyne-based mGlu 5 NAM developed by Wyeth. 35 This toxicity was believed to be linked to the reactivity of the alkyne based on metabolic studies that revealed extensive glutathione conjugation. 35 While this type of biotransformation does not always manifest in humans with alkyne-containing compounds, 25,27 many research groups have sought to design novel mGlu 5 NAMs that are outside of this chemotype.…”
Section: Introductionmentioning
confidence: 99%
“…35 This toxicity was believed to be linked to the reactivity of the alkyne based on metabolic studies that revealed extensive glutathione conjugation. 35 While this type of biotransformation does not always manifest in humans with alkyne-containing compounds, 25,27 many research groups have sought to design novel mGlu 5 NAMs that are outside of this chemotype. 4,5 We have actively pursued a variety of approaches toward that end over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for MPEP effects on NR2B-containing NMDA receptors [37], which may explain its inhibition of the development of opioid tolerance. There remains interest in developing therapeutic negative allosteric modulators that selectively target mGluR5 [14; 65]. However, higher doses of systemically delivered MPEP (100 mg/kg) and the analog MTEP (30–100 mg/kg) resulted in reduction of locomotor activity and impairment of rotarod performance[68].…”
Section: Discussionmentioning
confidence: 99%